Diálogo e amorosidade em Paulo Freire: dos princípios às atitudes na formação de professores - Toniolo, Joze Medianeira dos Santos de Andrade (2010)
This Master's Degree research Dissertation in Education, developed in the Formation Line, Knowledge and Professional Development (PPGE/UFSM) aims to contribute with theoretical and epistemological subsidies for the formation of teachers, based on Freire's propositions of loveliness and dialogue. This research is characterized as a qualitative type research, of theoretical-bibliographical character, having as fundamental speaker Paulo Freire, the main reference in this Dissertation. Starting with the theoretical-bibliographical deepening, it was developed an epistemological seam between the dialogues and the readings performed on education, formation of teachers (FREIRE, 1987; ARROYO, 2004), dialogue and loveliness (FREIRE, 1987, 1998, 1996). It was in the dialogue with different authors, especially with Paulo Freire and his arrow-words (CORAZZA, 2002), that I started giving form to my walker journey in the research, taking from the theoretical field some key concepts to understand how the principles of the loveliness and dialogue, based on the Freire's assumptions, can contribute to the formation of teachers. This investigation was intended to stimulate reflections on the practices and attitudes in everyday teaching and in the teacher's lives, in the perspective of an education that considers the loveliness and the dialogue as fundamental elements in any educational activity. The relevance of this research is focused on the loving and dialog perspective, that was so defended and experienced by Paulo Freire in education, inciting us to (re)build, (re)invent, (re)discover ways to (re)educate and (re)educate it, where our concepts are no longer just speeches and become effective practices, seeking to diminish the distance that separates our principles from our attitudes.